Situation Report: Romania, 5 September 1979 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Ceausescu, Assad, and Arafat Personnel Changes Affect Ministries , National Councils New Regulations on Food Travelers May Take Abroad Romania Soccer - Failures and Their Causes Concerted Protest against Writers' Union Awards Writers Question "Patriotic" Campaign Hoxha on Ceausescu